2013
DOI: 10.1192/pb.bp.112.039289
|View full text |Cite
|
Sign up to set email alerts
|

Readmission after discharge from a medium secure unit

Abstract: Aims and methodWe examined readmission to psychiatric hospital of 550 patients discharged from one medium secure unit over 20 years. Multiple sources were used to obtain readmission data.ResultsReadmission was common, particularly to non-secure psychiatric hospitals. At least 339 patients (61.6%) were readmitted to any psychiatric hospital (mean follow-up 9.5 years), with over a third (37.6%) subsequently being readmitted to medium- or high-security or both. Of those discharged directly to the community, havin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
11
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 16 publications
(18 reference statements)
2
11
1
Order By: Relevance
“…Multivariable analysis indicated that non-white ethnicity, early childhood maladjustment, and clozapine treatment were all significant independent predictors of time to recall. The average time to recall decreased with consecutive periods of readmission; this is consistent with previous research into returns to hospital in a Canadian sample of forensic patients [9].The rate of recall observed in the current study (45%) is higher than rates observed in previous UK and New Zealand studies (12-35%)[6,10,11], which may be due to differences in the length of follow-up, variations in recall versus readmission practices across study settings, and changes in thresholds for readmission/recall over time and across jurisdictions. Re-hospitalisation does not necessarily reflect treatment failure; it can be argued that a low threshold for recall is justifiable in this population; giving patients the chance to demonstrate their ability to manage community living whilst providing public reassurance.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…Multivariable analysis indicated that non-white ethnicity, early childhood maladjustment, and clozapine treatment were all significant independent predictors of time to recall. The average time to recall decreased with consecutive periods of readmission; this is consistent with previous research into returns to hospital in a Canadian sample of forensic patients [9].The rate of recall observed in the current study (45%) is higher than rates observed in previous UK and New Zealand studies (12-35%)[6,10,11], which may be due to differences in the length of follow-up, variations in recall versus readmission practices across study settings, and changes in thresholds for readmission/recall over time and across jurisdictions. Re-hospitalisation does not necessarily reflect treatment failure; it can be argued that a low threshold for recall is justifiable in this population; giving patients the chance to demonstrate their ability to manage community living whilst providing public reassurance.…”
supporting
confidence: 90%
“…Outcome studies of patients admitted to secure hospitals have focused predominantly on reconviction rates [5]. Where readmission to psychiatric hospitals has been assessed, rates are high [6]. The National Cohort Study in England and Wales followed patients for an average of 6.6 years (range six months-14 years) and found that 75% of forensic patients required at least one readmission following discharge from medium secure care [7].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This group was made up of 49 patients with an index offense of homicide and another 24 patients with an index offense of attempted homicide. The overall outcome of this series has already been described in a series of papers (Clarke, Davies, Hollin, & Duggan, 2011;Clarke et al, 2013;Davies, Clarke, Hollin, & Duggan 2007) indicating that their course after discharge was poor with a greatly increased mortality together with rates of reconviction and readmission of 50% and 40%, respectively. Davies et al (2007) give in detail the characteristics of these patients.…”
Section: Homicide Case Samplementioning
confidence: 97%
“…In all, 15 (24.2%) patients from the homicide group and 13 (18.3%) from the control group were readmitted to Arnold Lodge at least once: 2 patients from the homicide group and 3 patients from the control group were readmitted twice and 1 patient from each group was readmitted 3 times. Further readmission information for the full cohort is available in Clarke et al (2013).…”
Section: Readmissionmentioning
confidence: 99%